Clinical characteristics and outcomes of acute coronary syndrome patients with intra-aortic balloon pump inserted in intensive cardiac care unit of a tertiary clinic - Mert İlker Hayıroğlu; Yiğit Çanga; Özlem Yıldırımtürk; Emrah Bozbeyoğlu; Ayça Gümüşdağ; Ahmet Okan Uzun; Koray Kalenderoğlu; Muhammed Keskin; Göksel Çinier; Murat Acarel; Seçkin Pehlivanoğlu (KARE Publishing, 2018)
Objective: An intra-aortic balloon pump (IABP) is a mechanical support device that is used in addition to pharmacological treatment of the failing heart in intensive cardiac care unit (ICCU) patients. In the literature, there are limited data regarding the clinical characteristics and in-hospital outcomes of acute coronary syndrome patients in Turkey who had an IABP inserted during their ICCU stay. This study is an analysis of the clinical characteristics and outcomes of these acute coronary syndrome patients. Methods: The data of patients who were admitted to the ICCU between September 2014 and March 2017 were analyzed retrospectively. The data were retrieved from the ICCU electronic database of the clinic. A total of 142 patients treated with IABP were evaluated in the study. All of the patients were in cardiogenic shock following percutaneous coronary intervention, at the time of IABP insertion. Results: The mean age of the patients was 63.0+-9.7 years and 66.2% were male. In-hospital mortality rate of the study population was 54.9%. The patients were divided into 2 groups, consisting of survivors and non-survivors of their hospitalization period. Multivariate analysis after adjustment for the parameters in univariate analysis revealed that ejection fraction, Thrombolysis in Myocardial Infarction flow score of ≤2 after the intervention, chronic renal failure, and serum lactate and glucose levels were independent predictors of in-hospital mortality. Conclusion: The mortality rate remains high despite IABP support in patients with acute coronary syndrome. Patients who are identified as having a greater risk of mortality according to admission parameters should be further treated with other mechanical circulatory support devices.